Financial centre bias in sub-sovereign credit ratings - Ioannou, S; Wojcik, D; Pazitka, V (Elsevier, 2020)
We investigate whether credit rating agencies are biased towards areas with strong financial centre characteristics, using data for 259 areas from 39 countries for 2004–17. We employ a range of measurements of financial centre characteristics, including a financial centre index, the share of financial and business services in an area’s total employment, and revenues from investment banking. For all financial centre proxies, our results confirm the existence of a ‘financial centre bias’ that is statistically and economically significant. For example, cities present in the global financial centre index have a rating about a category higher than would be justified by fundamentals.